Pregnancy outcomes in women with a history of immunoglobulin A vasculitis. (24th December 2018) - Nossent, Johannes; Raymond, Warren; Keen, Helen; Inderjeeth, Charles; Preen, David
Abstract: Objectives: Case series suggest an increased risk of pregnancy complications in women with a history of IgA vasculitis (IgAV); however, no large quantitative studies have examined this possible association to date. We compared pregnancy rates and outcomes between female IgAV patients and controls and assessed flare risk of IgAV during pregnancy. Methods: Using state-wide hospital morbidity data we compared rates for live birth, preterm birth, abortive outcome and gestational complications between female IgAV patients (International Classification of Diseases-9-Clinical Modification 287.0; International Classification of Diseases-10-Australian Modification D69.0) ( n = 121) and non-exposed age-matched controls ( n = 284) in Western Australia. Results presented are means compared by Kruskal–Wallis test and proportions with odds ratios (ORs) (95% CI) compared by χ 2 testing. Results: There were 247 pregnancies in IgAV patients during which no disease flares were recorded and 556 pregnancies in controls. IgAV patients were younger at first pregnancy (24.7 vs 27.0 years, P < 0.01) and had 43 unsuccessful pregnancies (17.4%) and 204 live births with 17 preterm deliveries (8.3%). Women with IgAV had increased odds of spontaneous abortion (OR 1.9, 95% CI 1.1, 3.1, P = 0.04), preterm delivery (OR 2.0, 95% CI 1.1, 3.9, P = 0.02) and gestational hypertension (OR 4.7, 95% CI 2.3, 9.8). While gravidity did not differ (mean pregnancy number 2.4 vs 2.3, P = 0.36), IgAV patients had over a two-fold greater number of obstetric visits than controls (5.1 vs 2.5, P < 0.01). Conclusions: Hospitalization for IgAV has little impact on fertility and IgAV rarely flares during pregnancy. However, a history of IgAV associates with increased odds of spontaneous abortions, gestational hypertension and preterm delivery.